Microsoft defender for cloud - Diogenes, Yuri; Janetscheck, Tom (Pearson Education, 2023)
Microsoft Defender for Cloud offers comprehensive tools for hardening resources, tracking security posture, protecting against attacks, and streamlining security management all in one natively integrated toolset. Now, leading Microsoft security experts Yuri Diogenes and Tom Janetscheck help you apply its robust protection, detection, and response capabilities throughout your operations, protecting workloads running on all your cloud, hybrid, and on-premises platforms. This guide shows how to make the most of new components, enhancements, and deployment scenarios, as you address todays latest threat vectors. Sharing best practices, expert tips, and optimizations only available from Microsofts Defender for Cloud team, the authors walk through improving everything from policies and governance to incident response and risk management. Whatever your role or experience, theyll help you address new security challenges far more effectively -- and save hours, days, or even weeks.